2020
DOI: 10.3390/ijerph17020576
|View full text |Cite
|
Sign up to set email alerts
|

Affiliate Stigma and Related Factors in Family Caregivers of Children with Attention-Deficit/Hyperactivity Disorder

Abstract: This cross-sectional questionnaire study examined factors related to affiliate stigma among caregivers of children with attention-deficit/hyperactivity disorder (ADHD) and the association of affiliate stigma with caregivers’ unfavorable attitude toward ADHD and moderators. The affiliate stigma of 400 caregivers of children with ADHD was assessed using the Affiliate Stigma Scale. Caregivers’ and children’s factors related to affiliate stigma were examined using multiple regression analysis. Associations of affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 51 publications
3
27
0
5
Order By: Relevance
“…Chang et al [ 17 ] recruited 400 caregivers who were taking care of a child diagnosed with attention-deficit/hyperactivity disorder (ADHD) in Taiwan. Their findings indicated that caregivers’ affiliate stigma is a significant factor associated with their unfarmable attitudes toward the ADHD diagnosis and related treatments.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…Chang et al [ 17 ] recruited 400 caregivers who were taking care of a child diagnosed with attention-deficit/hyperactivity disorder (ADHD) in Taiwan. Their findings indicated that caregivers’ affiliate stigma is a significant factor associated with their unfarmable attitudes toward the ADHD diagnosis and related treatments.…”
Section: Findings Of the Contributions In The Special Issuementioning
confidence: 99%
“…Affiliate Stigma in Caregivers of Children with Attention-Deficit/Hyperactivity Disorder Affiliate stigma refers to the self-stigma of caregivers of people with mental illnesses; this stigma entails a caregiver perceiving stigmatizing attitudes being directed at them from others and internalizing these negative attitudes [1]. Affiliate stigma is prevalent among caregivers of children with attention-deficit/hyperactivity disorder (ADHD) [2][3][4]. Research has demonstrated that higher affiliate stigma among caregivers of children with ADHD is associated with more negative parenting [4] and increased distress [3] and depression [5] in caregivers.…”
mentioning
confidence: 99%
“…Higher parental affiliate stigma was also significantly associated with children's poorer social skills and greater aggression [4]. Caregivers of children with ADHD who have high affiliate stigma are more likely to have unfavorable attitudes toward their children's ADHD diagnosis, pharmacotherapy, behavioral therapy, as well as etiological explanations of ADHD [2]. Evaluating affiliate stigma and determining how to reduce it are crucial in promoting mental health in caregivers and their children with ADHD.…”
mentioning
confidence: 99%
“…While the participants noted high rates of compliance with the use of pharmaceutical interventions, they emphasized the significant role of the OT in providing information regarding medication, as well as supporting parents through the process of trial and error. Stigma has been frequently cited as a barrier for parents to access mental health treatment, with low levels of stigma, along with parental knowledge, predicting a positive attitude regarding ADHD diagnosis and treatment [46,47]. Corcoran et al [43] document the ambivalence parents have regarding the decision to medicate their ADHD child and the many factors which may affect this decision, including the availability of support and information from the health care system.…”
Section: Discussionmentioning
confidence: 99%